2017
DOI: 10.1038/eye.2017.262
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of preoperative steroid for rhegmatogenous retinal detachment with associated choroidal detachment

Abstract: PurposeTo investigate the effect of preoperative steroid on anatomical and functional outcomes of vitrectomy in patients with rhegmatogenous retinal detachment with associated choroidal detachment (RRD-CD), a rare but particular type of RRD.Patients and methodsThis retrospective cohort study included RRD-CD patients at Siriraj Hospital during January 2005 to December 2014. Patients with preexisting uveitis or RRD with giant retinal tears were excluded. Preoperative, intraoperative, and postoperative data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 19 publications
4
26
1
Order By: Relevance
“…Postoperative follow-up showed the retina was well attached without any visible retinal tear or hole. Even this case was not inclued in the single operation success list, this result is still comparable to those reports with preoperative steroids, that is from 51% to 81.8% [2,3,5,8,[13][14][15] ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Postoperative follow-up showed the retina was well attached without any visible retinal tear or hole. Even this case was not inclued in the single operation success list, this result is still comparable to those reports with preoperative steroids, that is from 51% to 81.8% [2,3,5,8,[13][14][15] ].…”
Section: Discussionsupporting
confidence: 81%
“…Literature search showed that most of these studies mainly evaluated the effects of preoperative administration of steroids between different routes: systemic or periocular or intravitreal administration. But only two of these studies compared the effects of preoperative steroids to steroids-sparing treatment, and they showed contradict results [2,5] Study conducted by Denwattana et al [5] disclosed that preoperative steroid treatment can significantly improved CD before vitrectomy, but seemed not to improve the single-operation retinal reattachment rate or visual acuity at 3 months when compared to no steroid treatment in RRD/CD patients. It seems that although preoperative steroids can help controlling inflammation, it may be not as so important as we once thought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their main characteristics and results are shown in Table 1. Four had a prospective design but only two of these were randomized; the other three of the seven studies were retrospective [27][28][29][30][31][32]. Our systematic review found that CCS are widely used preoperatively in addition to surgery to treat patients affected by RRD associated with choroidal detachment (CD) [27][28][29][30][31][32].…”
Section: Preoperative Usementioning
confidence: 99%
“…Anatomically, it makes the insertion and placement of trocar cannulas for pars plana vitrectomy (PPV) time-consuming and technically challenging. Various adjuvant techniques have been proposed to solve these problems, including the administration of steroids, sclerotomy to create passive drainage of the SCF, increasing IOP with an intravitreal injection of balanced saline solution (BSS), and penetration with a longer trocar (6 mm) [ 7 13 ]. The theoretical risks include the side effects of the drug and iatrogenic trauma of the transparent lens, which might consequently increase surgical difficulty and worsen patient prognosis.…”
Section: Introductionmentioning
confidence: 99%